NPC1 as a Modulator of Disease Severity and Viral Entry of SARSCoV- 2 - Vial, Cecilia; Calderón, Juan F.; Klein, Andrés D. (Current Molecular Medicine, 2021)
The COVID-19 plague is hitting mankind. Several viruses, including SARS-CoV-1, MERS-CoV, EBOV, and SARS-CoV-2, use the endocytic machinery to enter the cell. Genomic variants in NPC1, which encodes for the endo-lysosomal Niemann-Pick type C1 protein, restricts the host-range of viruses in bats and susceptibility to infections in humans. Lack of NPC1 and its pharmacological suppression inhibits many viral infections including SARS-CoV-1 and Type I Feline Coronavirus Infection. Antiviral effects of NPC1-inhibiting drugs for COVID-19 treatment should be explored.
Keywords: SARS-Cov-2